DISCLOSURE ON CORPORATE WEBSITES: CORPORATE SOCIAL RESPONSIBILITY IN MALAYSIA & SINGAPORE GOVERNMENT- LINKED COMPANIES - Esa, Elinda; Zahari, Abdul Rahman (Journal of Technology Management and Business, 2017)
This paper examines the current state of sustainability disclosure by focusing on information disclosed in the corporate websites of Malaysia and Singapore government-linked companies (GLCs) rather than through corporate annual reports. Content analysis is used to examine CSR disclosure in the websites of Malaysia and Singapore GLCs. Paired sample t-test was performed to identify the differences in the extent of CSR disclosure among websites of Malaysia and Singapore GLCs. Items disclosed under human resource theme are the most popular and high ranked disclosed among website of Malaysia GLCs while issues on the environment are more popular disclosed among website of Singapore GLCs. The paired sample t-test showed that there was no significant difference in CSR items disclosed on websites of Malaysia and Singapore GLCs. The findings imply that both GLCs in these countries relied on the precision of the website function as a good medium to communicate with their stakeholders as well as they conceived that the greater disclosure on firmâ€™s contribution to social welfare, the better reputation they will receive.Â